Writing online : a student's guide to the Internet and World Wide Web - Crump, Eric.; Carbone, Nick. (Boston : Houghton Mifflin, 1998)
Introduction to the online world. Netiquette. Preparing to enter the Internet. Electronic mail. Mailing lists. Telnetting on the Internet...
Keywords: English language; Rhetoric; Report writing; Internet; English language -- Rhetoric -- Computer network resources; Academic writing -- Computer network resources; Online data processing; World Wide Web